1998
DOI: 10.1023/a:1008384814079
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although blacks were more likely than whites to have diabetes as a primary diagnosis and blacks' educational level was lower than that of whites, all the statistically significant quality of life differences identified in this elderly cohort showed better quality of life among black patients than among white patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In line with previous findings, non-White patients experience lower fatigue and are less likely to experience an increase in fatigue over time in this patient population (Jhamb et al, 2009(Jhamb et al, , 2011Kutner & Devins, 1998;Kutner et al, 2000Kutner et al, , 2005, possibly as a result of cultural differences in perception of the illness and treatment (Unruh et al, 2004), variations in coping styles employed (Bhui et al, 2011;Prelow et al, 2000;Triandis et al, 1984), or due to stigma associated with disclosing distress and maladjustment (Cooper-Patrick et al, 1997;de Crane & Spielberger, 1981;Thompson et al, 2004). Education and health literacy are also likely to be important confounders here.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous findings, non-White patients experience lower fatigue and are less likely to experience an increase in fatigue over time in this patient population (Jhamb et al, 2009(Jhamb et al, , 2011Kutner & Devins, 1998;Kutner et al, 2000Kutner et al, , 2005, possibly as a result of cultural differences in perception of the illness and treatment (Unruh et al, 2004), variations in coping styles employed (Bhui et al, 2011;Prelow et al, 2000;Triandis et al, 1984), or due to stigma associated with disclosing distress and maladjustment (Cooper-Patrick et al, 1997;de Crane & Spielberger, 1981;Thompson et al, 2004). Education and health literacy are also likely to be important confounders here.…”
Section: Discussionsupporting
confidence: 85%
“…As the model included adjustment for patient's weight, these associations were independent of the gender and race weight differences. The association of race [27,28,29,30,31] and gender [32,33,34,35] with QOL in HD patients have long been noted. These may be secondary to spiritual beliefs [28], social factors [31,] psychological factors [29,34,35], how different genders or ethnic groups perceive their health level, or to different health expectations [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving patients who receive HEMO in the USA found that African Americans reported higher SF-36 total scores than white Americans. [28323334] Variation across cultures may illustrate disparities in the management of disease in different countries. [24] The differences in the findings with regard to the ethnicity variable could stem from possible inadequate sensitivity of SF-36 to the effect of differences on QOL.…”
Section: Discussionmentioning
confidence: 99%